Profile Analysis of Gifted Student Selection in Excellent Schools in Indonesia - Febriani, Afifah; Wiza, Rahmi; Adlin Binti Wan Aminudin, Wan Sofea (International Journal of Multidisciplinary Research of Higher Education, 2023)
The study of academically gifted students has attracted the attention of many researchers in the world in the last two decades. The existence of gifted students in this category always appears in schools even though it does not have an enormous population like other average students. Gifted students are those with eminent academic abilities, characterized by strong self-resistance, high learning motivation, unlimited academic reasoning and other advantages. However, in Indonesia, the study of academically gifted students has not been widely conducted by academics and studies related to this issue are still limitedly published. This research aims to find out the profile of gifted students in excellent schools that organize international class programs in Indonesia. This research employs a qualitative method with a case study approach. Data sources are taken through in-depth individual and group interviews with ten informants consisting of the principal, vice principal for curriculum, Islamic religious education teacher and students who study in international classes using Indonesian and English. All data are analyzed thematically using the Miles & Huberman interactive analysis model technique. The research findings found six categories of gifted student profile selection. The six categories are; i) having an IQ above 130, ii) high creativity, iii) critical thinking, iv) eagerness to do challenges, v) good language skills, vi) good language framework. These findings can be used as a reference for schools and teachers in determining gifted students before they are grouped in the international class program at school.